LAPORAN KEUANGAN BADAN AMIL ZAKAT NASIONAL (BAZNAS): PERSPEKTIF AKUNTANSI SYARIAH DAN PENCEGAHAN FRAUD - Rohemah, Riskiyatur; Alim, Mohammad Nizarul (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The Indonesian Institute of Accountants (IAI) as an accounting professional organization in Indonesia striven to contribute in the context of realizing a good accounting system for an OPZ, through the published of PSAK 109. This study aims to analyze and qualitatively the application of PSAK No. 109 on BAZNAS. This study used descriptive qualitative method. The data used in this research is secondary data. Secondary data is obtained from the financial statements of BAZNAS. Based on the data that has been obtained and the results of the analysis conducted by researchers through the analysis of the application of PSAK No. 109 in the financial statements of BAZNAS, that the financial statements of BAZNAS are due with PSAK No. 109 in terms of recording and completeness of its financial statements, although it does not include non-halal fund transactions. However, it is still necessary to improve the computerized system on financial reporting and monitoring system to prevent fraud in the financial statements presented so as to achieve public trust and transparency in publishing information about the financial statements.